Effect Of Green Marketing And Green Image On Green Satisfaction At Soekarno-Hatta International Airport - Raden Muhammad Zulkipli; Azwardi; Muchsin Saggaff Shihab (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of green marketing and green image on green satisfaction among users of Soekarno-Hatta International Airport. Data was collected from 280 airport users through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4. Results show that green marketing and green image positively and significantly affect green satisfaction, with green image emerging as the stronger predictor. The findings suggest that sustainable operational practices, supported by effective environmental communication, can strengthen the airport’s green image and improve passenger satisfaction. This study extends green marketing research in the airport sector and informs sustainable airport management. Keywords: Green Marketing; Green Image; Green Satisfaction; Green Airport; Soekarno-Hatta International Airport